A new hypothalamic substance, and not luteinizing hormone-releasing hormone, is detected immunocytochemically by antibody to luteinizing hormone-releasing hormone. - Sternberger, L A (1981)
Adjacent paraffin sections of rat hypothalami fixed in Bouin's fluid were treated either with buffer or with luteinizing hormone-releasing hormone (LHRH) before immunocytochemical staining with anti-LHRH. Upon buffer pretreatment, pituitary gonadotrophs were unstained and hypothalamic fibers were stained. Upon LHRH pretreatment, pituitary gonadotrophs were stained (receptor reaction) and hypothalamic fibers were unstained. Extension of washes and use of series of neutralizing antisera between LHRH application and immunocytochemical staining, as well as the absence of inhibiting concentrations of LHRH in the later washes and neutralizing antisera removed from the sections, excluded the possibility that the disappearance of visualization of hypothalamic fibers was due to blockage of anti-LHRH in immunocytochemical staining. The results suggested that LHRH removed from the sections an immunocytochemically stainable but as yet unknown analog of LHRH and replaced it with LHRH, which in turn became lost during subsequent immunocytochemical processing. This idea was confirmed by the isolation by high-pressure liquid chromatography of a peak, distinct from LHRH, upon treatment of hypothalami with LHRH. It is suggested that the new substance may be carrier-held and that this substance, rather than LHRH, is normally detected by immunocytochemistry with anti-LHRH. Added LHRH binds not only to high-affinity pituitary receptors but also to low-affinity hypothalamic carriers.